EFFECT OF ROASTING TIME ON THE ACIDITY LEVEL OF ARABICA COFFEE POWDER (COFFEE ARABICA): PENGARUH LAMA PENYANGRAIAN TERHADAP TINGKATKEASAMAN BUBUK KOPI ARABIKA (COFFEA ARABICA) - Endiyani; Renita Sri Syafitri; Umar Husein Abdullah; Mulla Kemalawaty (PT. ROCE WISDOM ACEH, 2024)
Coffee is one plantation crop that has long been cultivated and has a fairly high economic value. Data on world and domestic market demand for coffee commodities is increasing. World coffee production for arabica type is 60% and the remaining 40% is robusta type coffee. The key to the ground coffee production process is roasting. This process is the stage of forming the aroma and distinctive flavor of coffee from coffee beans with heat treatment. This study aims to determine the effect of the length of roasting carried out in the processing of coffee beans on changes in the acidity level of coffee powder. Data collection and analysis in this study used a non-factorial complete randomized design (CRD). The coffee roasting process uses a temperature of 1800 C with a roasting time of 20, 40, and 60 minutes with 3 repetitions. The results obtained showed that the acidity level of coffee powder decreased until it was close to neutral, namely P1 = 5.65%, P2 = 5.94%, and P3 = 6.27%.